Evaluation of rock burst hazard in fully mechanized mining face and separate source prevention and control technology - Yang, Yanbin; Gu, Wenzhe; Fang, Jialiang; Zhang, Shuai; Zhang, Beiyan (Frontiers in Materials, 2025)
To ensure safe and efficient mining at the 41,109 working face of Dafosi Mine, a systematic study was conducted focusing on key issues in rockburst prevention and control, using the 41,109 working face as the research context. First, an analysis of rockburst influencing factors was performed, proposing the use of a comprehensive index method to evaluate the rockburst hazard level of the working face. Based on the evaluation results, the working face was further divided into rockburst hazard zones. A source-specific monitoring and early warning system for rockburst was established targeting different hazard sources, accompanied by corresponding prevention and control measures. The research results show that when the comprehensive index method is applied to evaluate the rock burst risk of the 41,109 working face in Dafosi Coal Mine by considering both geological and mining factors, the risk evaluation index is 0.429, corresponding to a weak rock burst risk level. Centering on the two primary shock-inducing factors—roof dynamic loading and surrounding rock static loading—a source-specific monitoring and early warning system combining “regional monitoring + localized monitoring” was successfully established. By rationally deploying microseismic monitoring equipment, acoustic emission devices, and borehole stress monitoring systems, a source-specific prevention plan for the working face was designed. Ultimately, deep-hole pre-blast and large-diameter borehole pressure-relief measures were implemented on the roof. Concurrently, microseismic equipment monitored effectiveness, reducing microseismic energy by 54% compared to pre-treatment levels. This effectively controlled rockburst risks, ensuring safe and efficient mining operations at the working face with excellent on-site application results.